(untitled) (Research, Society and Development, 2022)
This study deals with the trajectories of indigenous Kaingang university students from communities located in the Alto Uruguai region, on the border between the Brazilian states of Rio Grande do Sul and Santa Catarina. Methodologically, it carries out a theoretical discussion based on decolonial literature (hooks, Fanon, Quijano, Sousa Santos, Spivak, Walsh) and on the philosophy of alterity (Biesta, Gur-Ze’ev, Larrosa, Levinas, Masschelein, Simons) on the western-centric epistemological hegemony in the educational processes and on the place at school based on reports of school experiences of indigenous young people enrolled in undergraduate courses at the Chapecó Campus of the Federal University of Fronteira Sul. It concludes on the importance of the school, as long as it is taken from a decolonial epistemological perspective, as a space-time to create and experience other and alteritarian ways of being and living with the other, as a time-space of hospitality, care and affirmation of the indigenous identity and to the construction of a more democratic and pluralistic society.